PENINGKATAN PARTISIPASI DAN PRESTASI BELAJAR PPKN DI MASA PANDEMI COVID 19 DENGAN WHATSAPP GROUP DAN YOUTOBE - Mugiraharjo, Hartoyo (Jurnal Analisis Pendidikan Sosial, 2024)
A long distance learning is an approach which has to be established on Covid 19 pandemic era. Various challenges and long distance learning constraints influence learning achievement, findings in the long distance learning evaluation on initial period are decreasing the learning participation and decreasing the ‘KKM (Minimum Completeness Criteria)’ completeness Percentage. This article describes how to increase participation and that completeness percentage on the Long Distance learning through WAG usage. The stages in Classroom Action Research (CAR) are planning, action, observation, and reflection. The results of the research show that: (1) The WhatsApp usages are able to increase students’ achievement in ‘KKM’ completeness. Students’ participation is increasing; In cycle I, the 1st meeting is 46,88%. In cycle I in the 2nd meeting, it increases into 65,63%. The active participation in cycle 2 in the 1st meeting is 87,50% and in the 2nd meeting becomes 90,63%. The learning achievement in cycle I is 74.38%. In the cycle II, It increases into 80,41. There are 30 of 32 Students who are able to fulfill ‘KKM (Minimum Completeness Criteria)’ 75 or 80,72%.